Can We Predict Poor Hemodynamic Tolerance of Intermittent Hemodialysis With Echocardiography in Intensive Care Patients?. (1st December 2014) - Chimot, Loïc; Gacouin, Arnaud; Nardi, Nicolas; Gros, Antoine; Mascle, Sophie; Marqué, Sophie; Camus, Christophe; Le Tulzo, Yves
Abstract : Objectives: Tolerance of intermittent hemodialysis is potentially poor for patients hospitalized in the intensive care unit, particularly those in shock. The aim of this study was to determine whether an evaluation of the hemodynamic state by echocardiography before an intermittent hemodialysis session could predict tolerance during the session. Methods: Before an intermittent hemodialysis session, transesophageal echocardiography was performed on sedated patients, and transthoracic echocardiography was performed on nonsedated patients. Poor tolerance during intermittent hemodialysis was defined by the following criteria: greater than 20% decrease in mean arterial pressure, need for fluid loading (≥500 mL), a 15% increase in catecholamine if the dose was stable before the session or doubling the speed of catecholamine infusion if necessary, arrhythmia, and the necessity to stop the session before its prescribed end. Results: A total of 54 patients were included: 20 (37%) were intubated under controlled mechanical ventilation (group 1) and underwent transesophageal echocardiography; 14 (26%) were intubated under pressure support ventilation (group 2) and underwent transthoracic echocardiography; and 20 (37%) had no ventilation support (group 3). Twenty‐four patients (46%) had poor tolerance criteria. A comparison of groups showed no significant difference in tolerance. Similarly, there was no difference with and without ultrafiltration. Increased respiratory variation of the vena cava was not predictive of poor tolerance in groups 1 and 2. In group 3, there was greater variation in patients with poor tolerance. In patients receiving mechanical ventilation, greater respiratory variability of the maximum velocity measured in the pulmonary artery was predictive of poor tolerance. Conclusions: The hemodynamic profile of patients receiving mechanical ventilation was unable to predict tolerance of an intermittent hemodialysis session. In patients without mechanical ventilation, hypovolemia before the session appeared to be predictive of poor tolerance.